2017
DOI: 10.1002/cnm.2889
|View full text |Cite
|
Sign up to set email alerts
|

Identification of dynamic load for prosthetic structures

Abstract: Dynamic load exists in numerous biomechanical systems, and its identification signifies a critical issue for characterizing dynamic behaviors and studying biomechanical consequence of the systems. This study aims to identify dynamic load in the dental prosthetic structures, namely, 3-unit implant-supported fixed partial denture (I-FPD) and teeth-supported fixed partial denture. The 3-dimensional finite element models were constructed through specific patient's computerized tomography images. A forward algorith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 60 publications
(125 reference statements)
0
3
0
Order By: Relevance
“…The authors also clarified that the load on the implant at gum chewing was basically larger than that at maximum voluntary clenching (MVC). Other studies [ 38 , 39 ] reported that the load magnitude was affected by food texture, and the load magnitude during chewing was larger than that during MVC. The data were subsequently used for advanced experimental and numerical purposes, such as finite element analysis (FEA), and the effect of peri-implant bone resorption on the stress distribution in implant body was investigated [ 40 ].…”
Section: Resultsmentioning
confidence: 97%
“…The authors also clarified that the load on the implant at gum chewing was basically larger than that at maximum voluntary clenching (MVC). Other studies [ 38 , 39 ] reported that the load magnitude was affected by food texture, and the load magnitude during chewing was larger than that during MVC. The data were subsequently used for advanced experimental and numerical purposes, such as finite element analysis (FEA), and the effect of peri-implant bone resorption on the stress distribution in implant body was investigated [ 40 ].…”
Section: Resultsmentioning
confidence: 97%
“…To meet the aforementioned requirements, several bite force sensor systems have been developed. (9,10) The sensor must be sufficiently thin not to interfere with occlusion to measure bite force in the maximal intercuspal position, which is the best-fit position of the opposing teeth. Furthermore, a wearable measurement system is required to monitor bruxism during sleep.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the measurement method in vitro, theoretical calculation represented by finite element method (FEM) with the advantages of controllable experimental conditions, low cost, and short experimental cycle is more and more popular in recent decades. [21][22][23][24] Various methods for orthodontic force simulation which applied external force loads to teeth or appliances can be found in literature. Liao et al 1 applied distally directed tipping and bodily forces to human maxillary to investigate optimal orthodontic force.…”
Section: Introductionmentioning
confidence: 99%